Compressibility characteristics of peat soil treated with MUF-P resin - Mohd Daud, Mohd Nazrin; Nik Daud, Nik Norsyahariati (Trans Tech Publications, 2021)
Peat is commonly described as a soil that is possess to high rate of compressibility due to present of high organic substance derived from plant origins. Peat soil naturally associated with settlement and consolidation characterized by its high initial void ratio, organic content and water holding capacity. This paper presents the performance of peat soil treated with powdered melamine urea formaldehyde resin (MUF-P) in term of compression and consolidation behaviour under standard compressibility test. In this study, series of one-dimensional oedometer test were carried out with the load increment method from 12.5 to 400 kPa after 24 hours of each loading. Peat soils under high moisture condition were mixed with MUF-P within 3 days of stipulated periods of curing times. The results indicate that increasing the MUF-P proportion has improved the compressibility characteristics of peat soil. The result shows the values of compression index (Cc) decreased from 4.12 to 0.9, and secondary compression index (Cα) were also decreased from the range of 0.026 to 0.320 to the range of 0.080 to 0.161 with the increase of peat MUF-P proportions up to maximum 350 kg/m3.